2004
DOI: 10.1136/adc.2003.031112
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of asthma and allergies in Singapore; data from two ISAAC surveys seven years apart

Abstract: Background and Aims: Over the past few decades, the prevalence of asthma has been increasing in the industrialised world. Despite the suggestion of a similar increase in Singapore, the 12 month prevalence of wheeze among schoolchildren in 1994 was 2.5-fold less than that reported in western populations. It was hypothesised that with increasing affluence in Singapore, the asthma prevalence would further increase and approach Western figures. A second ISAAC survey was carried out seven years later to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 22 publications
3
74
3
1
Order By: Relevance
“…The endotoxin levels were found to be significantly higher in rural Thailand than in urban Singapore. Though data on the atopic prevalence in the Thepa district has yet to be published, other studies provide evidence that the rates of allergic diseases in infants is higher in the more urbanized regions of South East Asia [4,5,6]. Our results show similar differences between urban and rural regions to those described by Riedler et al [7], which demonstrated higher endotoxin levels in farming environments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The endotoxin levels were found to be significantly higher in rural Thailand than in urban Singapore. Though data on the atopic prevalence in the Thepa district has yet to be published, other studies provide evidence that the rates of allergic diseases in infants is higher in the more urbanized regions of South East Asia [4,5,6]. Our results show similar differences between urban and rural regions to those described by Riedler et al [7], which demonstrated higher endotoxin levels in farming environments.…”
Section: Discussionsupporting
confidence: 80%
“…A similar observation has been made in urban communities compared with rural communities of ethnically identical societies [2, 3]. Again, in South East Asia, the prevalence of atopic diseases remains low in rural areas, such as Chiang Mai in Thailand, compared with urbanized metropolises such as Bangkok and Singapore [4,5,6]. …”
Section: Introductionmentioning
confidence: 59%
“…Our survey used telephone interviews in 11 cities across Mainland China and the response rate was 63.7%, which was close to the rate in the Israeli population (58.5%) [23] obtained using a similar methodology of a telephone questionnaire [20, 21]. In the ISAAC survey conducted in Singapore in 1994 and 2001, which used written questionnaires to collect data, the response rates were 90% in 1994 and 91% in 2001 [24], whereas rates were as low as 47–57% in New Zealand, depending on the mode of data collection [25]. Thus, the response rate observed in the current study was within the expected range, although inevitably there could be some selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that a family history of atopic disease constitutes an important factor in the genetic background. Environmental factors have been thought to be important in determining the subsequent development of asthma [24]. One of the most important extrinsic factors that influence children's health is passive smoking [25][26][27].…”
Section: Discussionmentioning
confidence: 99%